A rechargeable aqueous aluminum–sulfur battery through acid activation in water-in-salt electrolyte. Issue 13 (22nd January 2020) - Hu, Zhiqiu; Guo, Yue; Jin, Hongchang; Ji, Hengxing; Wan, Li-Jun
Abstract : A water-in-salt electrolyte is employed to give rechargeable aqueous Al–S batteries. Abstract : We demonstrated a rechargeable aqueous Al–S battery based on a water-in-salt electrolyte with the configuration Al‖Al(OTF)3 + LiTFSI + HCl‖S/C. The superconcentrated LiTFSI trapped water molecules to inhibit the hydrolysis of aluminum polysulfides in the cathode, and the HCl additive provided a mild acidic environment to enable repeatable oxidation–reduction reactions in the anode.